Microplastic-enhanced chromium toxicity in Scenedesmus obliquus: Synergistic effects on algal growth and biochemical responses - Luoxin Li; Jiani Yu; Yonghua Ma; Hui Tan; Fengxia Tan; Yi Chai; Hui Zhang (Ecotoxicology and Environmental Safety)
This study explores the combined toxicity of microplastics (MPs) and chromium (Cr6 +) on the freshwater green algae Scenedesmus obliquus. As emerging contaminants in aquatic ecosystems, MPs have been shown to intensify the toxicity of Cr6+, leading to a more significant impact on algal growth and biochemical responses than either stressor alone. A 30-day experimental simulation revealed that co-exposure to Cr6+ and 5 µm diameter polystyrene MPs resulted in significantly enhanced toxicity compared to individual exposures, characterized by a notable decrease in algal growth, diminished photosynthetic pigments, and protein content, alongside oxidative system damage. 100 nm MPs exhibited a distinct toxicity profile, with more pronounced effects when not combined with Cr6+, suggesting size-dependent interactions with algal cells. Transcriptomic analysis illuminated the complex regulatory mechanisms, indicating that toxicity primarily modulates metabolic pathways essential for photosynthesis, oxidative phosphorylation, the TCA cycle, and ribosome function in Scenedesmus obliquus. This study not only delineates the distinct toxicity effects of single and combined exposure systems but also emphasizes the need for a deeper understanding of the role of MPs in environmental pollution and their potential to modulate the toxicity of heavy metals in aquatic ecosystems.